2016
DOI: 10.3390/nu8080473
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Fat Mass and Fat-Free Mass with Physical Fitness in 4-Year-Old Children: Results from the MINISTOP Trial

Abstract: Physical fitness is a powerful marker of health in youth. Studies in adolescents and adults suggest that higher fat mass is related to worse physical fitness. However, there is limited knowledge whether fat mass and fat-free mass are associated with physical fitness already in preschoolers. Baseline data from the MINISTOP (Mobile-based INtervention Intended to STop Obesity in Preschoolers) trial was utilized for this cross-sectional analysis. Body composition was assessed using air-displacement plethysmography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
48
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 34 publications
13
48
1
2
Order By: Relevance
“…It could be assumed that overweight children avoid strenuous weight-bearing physical activities like running and prefer light physical activities. Overweight children had expectedly better results in handgrip strength, which is also reported in previous studies in preschoolers [6,15]. In the present study both higher BMI and FM weakened the results of weight-bearing physical fitness tests.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…It could be assumed that overweight children avoid strenuous weight-bearing physical activities like running and prefer light physical activities. Overweight children had expectedly better results in handgrip strength, which is also reported in previous studies in preschoolers [6,15]. In the present study both higher BMI and FM weakened the results of weight-bearing physical fitness tests.…”
Section: Discussionsupporting
confidence: 89%
“…It is not surprising that overweight children had significantly higher BMI values in our study. However, it is important to emphasize that BMI reflects both the FM and the FFM in the body, which may have different associations with physical fitness [6]. This opinion could explain the negative association between FFM and results of 20m shuttle run and 4x10m shuttle run in present study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…As a result, heavier children usually perform worse than their counterparts with lower body mass. In line with this, Henriksson et al 32 confirmed that a better performance on weightbearing tests in preschool children was associated with a lower fat mass index. The researchers concluded that the more favourable body composition you have, the fitter you are.…”
Section: Discussionmentioning
confidence: 72%
“…Physical fitness assessments were performed according to the validated PREFIT battery [2], a s evidenced by previous publications [13,35,36]. The details of each testing item were described as below:…”
Section: Measurementsmentioning
confidence: 99%